Analisis Seismisitas dan Energi Gempabumi di Kawasan Jalur Sesar Opak Oyo Yogyakarta - Nugroho Budi Wibowo; Juwita Nur Sembri (Department of Physics, Sebelas Maret University, 2017)
The earthquake that occurred in the Region of Yogyakarta caused by fault activity on the surface, such as Opak-Oyo Fault, Dengkeng Fault, Menoreh Fault and plate tectonic activity in South of Java. Opak-Oyo fault activity reflected from epicenter distribution and earthquake energy. This research aims to analyze the earthquake energy which has epicenter around the Opak-Oyo Fault in spatial and temporal. Based on earthquake catalog from 2008 – 2016, there were 66 earthquake with 11 significant event. Epicenter distribution reflected in seismicity map and for the tectonic parameter use least square method. Seismicity map of Opak Oyo Fault area show that distribution of epicenter in the East and Southeast of fault line with the calculation result of b value by least square method is 0.4. In temporal, there is an increasing trend of events in 2008-2015 and decline trend of earthquake in 2015- 2017. Earthquake energy that released in Opak Oyo Fault area has varies value about 1x105.2 – 1x1012joules. Meanwhile, the energy that associated with the existence of Opak Fault Lines has value between 1x105.2 – 1x109.6 Joule with 10-20 km of hypocenter.The distribution energy has similar pattern with geological formations in that area.